Solvent control of ligand-metal electron transfer in mononuclear copper complexes with redox-active bisguanidine ligands: this article is dedicated to Prof. Dr. Peter Comba on the occasion of his 65th birthday - Schrempp, David; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2018)
Intramolecular electron transfer (IET) processes between the metal and a redox-active ligand in a transition-metal complex are currently intensively studied, as they represent key steps of some redox-catalytic reactions in synthetic chemistry and of some enzymatic redox reactions in biological systems. Using a combination of experimental results and quantum chemical calculations, we herein examine in detail the role of the solvent polarity and seemingly small modifications at the redox-active ligand on IET processes in mononuclear copper complexes with redox-active bisguanidine ligands. A direct and simple correlation between the coordination mode and the electronic structure in these complexes is established, assisting in the fine-tuning of the ligand properties for optimal promotion of IET.
Gesehen am 23.04.2020